The Unsignaled Intersection Performance Analysis of Arterial Access Road at Karawang Barat 1Toll Gate, West Java - Luther Panangian Joseph; Andri Irfan Rifai; Mohamad Taufik (International Journal Labs, 2022)
An intersection is the confluence of different directions of the road. In general, traffic conflicts often occur in intersectional areas. Congestion can occur due to the dense volume of vehicles and the absence of traffic lights. This study aims to determine the performance of an uncited intersection in accommodating vehicles passing through it. What this means is that this unlicensed interchange does not cause congestion due to the irregularity of the driver of the vehicle. Primary data collection in this study was carried out directly, namely recording the size of the road width at the intersection and taking survey data on the number of vehicles directly at the intersection. After analyzing the calculation results, it was found that the road capacity value (C) was obtained at 3469 pcu/hour. This value is below the maximum base capacity (Co = 5144.42 smp/h). Based on the results of calculation analysis from survey data, it shows the value of the degree of saturation (DS) of 0.67 sec/pcu. If the degree of saturation (DS) is <0.70, then the degree of saturation at the intersection falls into the low category. In the calculation obtained, the probability of queuing at the intersection (QP) is 19 - 38%.